Characteristics of high-protein corn yogurt with the addition of soy protein isolate and spirulina - Dewi, Ratih Tiara; Aini, Nur; Haryanti, Pepita; Khairunnisa, Anita; Probowati, Banun Diyah; Arsyistawa, Hadana Sabila (JITIPARI, 2026)
Corn milk yogurt is a fermented product that has a low protein content. One of the efforts to increase the protein content of corn milk yogurt is by adding spirulina and soy protein isolate as a source of high protein. The objectives of this research are 1) to study the formulation of high protein corn milk yogurt with the addition of spirulina and soy protein isolate; 2) to study the characteristics of corn milk yogurt. Corn yogurt with the addition of spirulina (0.08, 0.12 and 0.16%) and soy protein isolate (4.5, 8.5 and 12.5%) were tested for physicochemical and sensory characteristics. Results revealed Corn yogurt addition with of 0.08-0.16% spirulina and 4.5 - 12.5% soy protein isolates have protein content of 1.94 - 7.04%, water content of 76.0-81.1%, fat content of 0.66 – 1.17%, 14.5-16.6% of carbohydrate content, viscosity of 328.3-1128.7 mPas, total solids 16.01-17.93oBrix, pH of 3.41-3.67, lactic acid bacteria of 51 x 107 CFU/ml – 76 x107 CFU/ml.  Corn yogurt has sensory characteristics including yogurt taste of 2.60-3.68, green color of 2.42-3.82, yellow color of 1.45-2.53, corn flavor 2.27-2.60, beany flavor 2.70-3.17, spirulina flavor 2.23-3.08, viscosity 2.62-3.82 and preference of 2.25-2.9. The best formulation for making corn yogurt is a combination treatment with 8.5% soy protein isolate concentration and 0.12% spirulina with a protein content of 5.41%. While yogurt is preferred, this formula still needs some fine tuning to eliminate the fishy scent caused by the spirulina